Burnout and organisational stressors among healthcare staff working with adults with intellectual disabilities in Ireland - Patrick Clancy; Marica Cassarino (PLoS ONE, 2025)
Background The associations between organisational stressors and burnout among healthcare staff working with adults with intellectual disabilities are underexplored. This study investigated rates of burnout and associated stressors among Irish healthcare workers during the COVID-19 pandemic. Materials and methods A convenience sample of 329 Irish frontline staff supporting adults with intellectual disabilities completed a survey assessing personal, work-related, and client-related burnout, and organisational stressors. Quantitative correlational analysis assessed bivariate and multi-variate associations, while qualitative accounts were analysed thematically. Results Compared to international data, we observed very high levels of personal and work-related burnout, with lower levels of client-related burnout. “Lack of resources” was the stressor holding the strongest association with burnout, followed by “bureaucracy” and “work-home conflict”. Qualitative responses highlighted the negative impact of the pandemic on workload, service quality, and staff wellbeing. Discussion Our findings highlight an important association between organisational stressors and burnout among frontline staff, suggesting the potential benefit of designing organisationally focused interventions to reduce stress and promote staff wellbeing.